2022
DOI: 10.1038/s41467-022-29367-5
|View full text |Cite
|
Sign up to set email alerts
|

Multiomic profiling of the acute stress response in the mouse hippocampus

Abstract: The acute stress response mobilizes energy to meet situational demands and re-establish homeostasis. However, the underlying molecular cascades are unclear. Here, we use a brief swim exposure to trigger an acute stress response in mice, which transiently increases anxiety, without leading to lasting maladaptive changes. Using multiomic profiling, such as proteomics, phospho-proteomics, bulk mRNA-, single-nuclei mRNA-, small RNA-, and TRAP-sequencing, we characterize the acute stress-induced molecular events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
70
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(80 citation statements)
references
References 121 publications
9
70
1
Order By: Relevance
“…Unpredictable chronic stress reduced the spontaneous running wheel activity of mice and maintained this reduction for up to 8 weeks [ 31 ]. Acute stress significantly reduced the movement distance and the central residence time of mice [ 32 ]. Our results also showed that the movement distance of mice decreased significantly with the extension of cold exposure at various temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Unpredictable chronic stress reduced the spontaneous running wheel activity of mice and maintained this reduction for up to 8 weeks [ 31 ]. Acute stress significantly reduced the movement distance and the central residence time of mice [ 32 ]. Our results also showed that the movement distance of mice decreased significantly with the extension of cold exposure at various temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis (AS) is the main cause of coronary heart disease, cerebral infarction, and peripheral vascular disease ( 11 ). Chronic stress is prevalent in modern society and causes many kinds of mental diseases ( 12 , 13 ). The main results of this study were that renal SGLT1 expression was increased in the case of chronic stress alone, but not statistically significant ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…SimBA (Nilsson et al, 2020 ) uses features extracted from DLC or SLEAP pose data as input to a random forest classifier to label mouse behaviors, such as sniffing (social behavior; Dawson et al, 2022 ), freezing (fear conditioning; Hon et al, 2022 ), and pup retrieval (Winters et al, 2022 ). DLCAnalyzer (Sturman et al, 2020 ) also includes capabilities for supervised behavior classification and has been used to track head dips in the EPM (Grimm et al, 2021 ) and head angle in the open-field test (von Ziegler et al, 2022 ). MARS combines pose estimation and behavior classification capabilities and is suitable for multi-animal social behavior analysis (e.g., attack, mounting; Segalin et al, 2021 ).…”
Section: Machine Learning Approaches For Emotional Behavioral Analysismentioning
confidence: 99%